2021
DOI: 10.1155/2021/6072155
|View full text |Cite
|
Sign up to set email alerts
|

The Rare Cases of Parotid Gland Arteriovenous Malformations

Abstract: Arteriovenous malformation (AVM) results from errors in vascular development during embryogenesis; absent capillary beds lead to shunting directly from the arterial to venous circulation. Although it is common in the head and neck region, AVMs located in the parotid gland are quite rare. Here, we report two cases of arteriovenous malformation of the parotid gland that presented to our out-patient setup with swelling in the parotid region and were diagnosed as arteriovenous malformation on histopathological stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…There was no recurrence or re-expansion of auricular AVMs after treatment. Among the 21 patients with parotid AVMs ( Table 3 ), the majority underwent surgical excision (8 patients) and embolization (5 patients), and embolization with sclerotherapy (4 patients), while a few patients underwent embolization followed by excision (3 patients), and only 1 had sclerotherapy [ 5 , 22 27 ]. Although no recurrence was detected in any of the AVM cases, there was incomplete involution in 3 cases (60%) of parotid AVMs following embolization [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…There was no recurrence or re-expansion of auricular AVMs after treatment. Among the 21 patients with parotid AVMs ( Table 3 ), the majority underwent surgical excision (8 patients) and embolization (5 patients), and embolization with sclerotherapy (4 patients), while a few patients underwent embolization followed by excision (3 patients), and only 1 had sclerotherapy [ 5 , 22 27 ]. Although no recurrence was detected in any of the AVM cases, there was incomplete involution in 3 cases (60%) of parotid AVMs following embolization [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The parotid region is not a typical location for VMs, with about 50 cases reported [ 10 ]. Achache et al demonstrated that, among 614 parotidectomy cases identified, there were only 10 cases of parotid VMs (1.6%).…”
Section: Discussionmentioning
confidence: 99%